Robustness of superconducting properties to transition metal substitution and impurity phases in Fe1-xVxSe - Kirschner, FKK; Woodruff, DN; Bristow, MJ; Lang, F; Baker, PJ; Clarke, SJ; Blundell, SJ (American Physical Society, 2019)
We have performed transverse- and zero-field muon spin rotation/relaxation experiments, as well as magnetometry measurements, on samples of Fe1-xVxSe and their Li+NH3 intercalates Li0.6(NH2)0.2(NH3)0.8Fe1-xVxSe. We examine the low vanadium substitution regime: x=0.005, 0.01, and 0.02. The intercalation reaction significantly increases the critical temperature (Tc) and the superfluid stiffness for all x. The nonintercalated samples all exhibit Tc≈8.5 K while the intercalated samples all show an enhanced Tc>40 K. Vanadium substitution has a negligible effect on Tc, but seems to suppress the superfluid stiffness for the nonintercalated samples and weakly enhance it for the intercalated materials. The optimal substitution level for the intercalated samples is found to be x=0.01, with Tc≈41K and λab(0)≈0.18μm. The nonintercalated samples can be modeled with either a single d-wave superconducting gap or with an anisotropic gap function based on recent quasiparticle imaging experiments, whereas the intercalates display multigap nodal behavior which can be fitted using s+d- or d+d-wave models. Magnetism, likely from iron impurities, appears after the intercalation reaction and coexists and competes with the superconductivity. However, it appears that the superconductivity is remarkably robust to the impurity phase, providing an avenue to stably improve the superconducting properties of transition metal substituted FeSe.